Six-DOF simulations of an underwater vehicle undergoing straight line and steady turning manoeuvres. (15th February 2018) - Kim, Howan; Ranmuthugala, Dev; Leong, Zhi Quan; Chin, Christopher
Abstract: This paper reports on numerical simulations conducted on an underwater vehicle for six-degrees of freedom (6-DOF) free running manoeuvres using Computational Fluid Dynamics (CFD). The CFD manoeuvring trials (straight line and steady turning manoeuvres) were conducted using a model-scaled BB2 submarine with movable control planes and a body force propeller represented by an actuator disk incorporating predetermined propulsion properties. The propulsion properties were obtained from captive self-propulsion simulation adopting the actual BB2 propeller. The free running simulations were validated against experimental data. The results showed that the 6-DOF CFD simulations are capable of predicting the BB2 manoeuvring characteristics with good agreement against the experimental data. The 6-DOF manoeuvring simulations carried out allow for the unsteady viscosity effects, which is usually a limitation of the traditional coefficient-based prediction method. The simulations will enable accurate determination of the vehicle's manoeuvring characteristics, which are essential for the control system design and its safe operating envelope. Highlights: URANS computations coupled with a Six-DOF RBD model are performed for manoeuvring simulation of an underwater vehicle. Simulation model employs a body force propeller and movable control planes realised by an overset grid technique. Straight line and steady turning manoeuvres are carried out at set propeller rotation speeds and control plane angles. Simulation results are compared against experimental data.